Integrating Digital Literacy into Sociolinguistics Class in MBKM Curriculum through Theory of Planned Behavior - Anin Eka Sulistyawati; Yuvita Yuvita; Sri Wardhani (Cakrawala: Jurnal Pendidikan, 2022)
Independent Learning Curriculum (MBKM) is arranged to improve the students’ competencies in the revolution industry 4.0. One of the important aspects in that curriculum is a broad knowledge of digital literacy. Integrating digital literacy into Sociolinguistics class in this study employed Project Based Learning (PBL) by creating posters and short learning video. The results of these assignments were analyzed through Theory of Planned Behavior by Ajzen. This case study aims to investigate the types of students’ beliefs on the use of integrating digital literacy into Sociolinguistics class. This study employed triangulation data; questionnaire, interview and observation. Those instruments were used to identify the process and results of integrating digital literacy into Sociolinguistics class through behavior belief, cognitive belief, normative belief, and control belief. The result of this study found students believe that the use of integrating digital literacy into Sociolinguistics class influenced heir strategy of learning. Thus, having a strong belief of integrating digital literacy shows the students’ perception to use digital technology in Sociolinguistics class